PENGUATAN KARAKTER MELALUI PEMBELAJARAN BERBASIS PROYEK PADA JENJANG SEKOLAH MENENGAH KEJURUAN - Ni Wayan Widyani (Al-SAMBASY: Jurnal Kajian Pendidikan, 2026)
The purpose of this study is to analyze the strengthening of students’ character through the implementation of project-based learning at the vocational high school level. The issue addressed is the suboptimal integration of character education into learning, which tends to focus on cognitive aspects. The research methodology employed is a qualitative descriptive study using field observations and a literature review. Data were obtained through direct observation of learning activities and a review of relevant literature. The study’s findings demonstrate that the application of project-based learning can foster active student engagement in the learning process while promoting the development of character values such as responsibility, cooperation, discipline, creativity, and social concern. Meanwhile, this approach also has a positive impact on changes in attitude, increased self-confidence, and students’ problem-solving skills. However, its implementation requires careful planning and consistent guidance from teachers to ensure optimal results. Thus, project-based learning can serve as an effective alternative for integrating character development into the educational process.